PENGARUH INFLUENCER, DISCOUNT DAN ONLINE PRODUCT REVIEW TERHADAP IMPULSIVE BUYING: STUDI PADA MEREK SCARLETT WHITENING - Sihombing, Geraldy Pesakhim; Widjaja, William (Jurnal Nusa Manajemen, 2025)
This study examines the influence of Influencers, discounts, and online product reviews on consumers’ impulsive buying behavior for the Scarlett Whitening brand. Data were collected through a quantitative survey of 385 Scarlett Whitening users on Shopee and analyzed using SEM-PLS. The results reveal that Influencers, discounts, and online product reviews significantly impact impulsive buying. Influencers drive purchases through trust and appeal, discounts through price reductions and promotion duration, and online product reviews through credibility and perceived usefulness. These findings offer strategic insights for beauty brand marketing to leverage these factors in promoting impulsive buying.